What Motivates Various Generations for Work? Dependency between Different Motivation Approaches, Engagement and Loyalty in the Workplace - Joanna NIEŻURAWSKA-ZAJĄC; Hanna Karaszewska; Iveta Ludviga (Communications of International Proceedings, 2021)
Despite the fact that both in theory and practice, a great deal of system solutions have been developed regarding employee motivation, research in recent years indicates a significant decrease in the level of employee involvement in the European Union (Trends in Global Employee Engagement, 2019). It is extremely problematic issue and causes difficulties in enterprises, generates an increase in costs, causes weaker work results and higher staff fluctuation. To prevent this, employers are looking for new solutions in the area of human resource management. Introducing a new motivation approach is becoming imperative in order to increase the level of engagement and loyalty among employees. In order to draw conclusions about relationships between non-measurable concepts based on non-experimental data a structural equation modelling approach was used. We report the results of a survey conducted in Poland among  900 people aged,  who were employed for at least  6 months (PL= 900). We found: dependency between different  motivation  approach, engagement and loyalty in  the workplace, especially between the involvement of employees and the concept of happiness at work - hygge. Funding: this article has been supported by the Polish National Agency for Academic Exchange under Grant No. PPI/APM/2019/1/00017/U/00001 project title: "The International Academic Partnership for Generation Z" – 2019-20201.
Keywords: Employee Motivation; Employee Engagement; Loyalty; Hygge; Structural Equation Modelling (PLS-SEM)